Study of Self-reducing Fe3+ Fenton-like System for Phenol-containing Coal Chemical Wastewater - Boyi CONG; Yang LIU; Haoxiang YIN; Heng ZHANG; Peng ZHOU; Wei LI; Bo LAI (工程科学与技术, 2024)
Coal chemical wastewater exhibits complex water quality, with a high concentration of difficult-to-degrade organic matter and ammonia nitrogen, posing significant challenges for wastewater treatment. Current technologies, including coagulation, adsorption, and membrane bioreactors, have limitations such as high costs, unstable operation, and suboptimal pretreatment effects, failing to meet the evolving needs of the coal chemical industry. This study introduces a novel method using the reducibility of phenolic organic compounds in coal chemical wastewater to enhance the Fe3+/Fe2+ cycle in the Fe3+/H2O2 Fenton-like system, thus efficiently treating the wastewater. Comparative experiments demonstrated that the Fe3+/H2O2 system achieves removal rates of COD, TOC, TN, and NH3–N at 74.63%, 52.62%, 10.46%, and 15.11%, respectively. This system significantly reduces coloration, shows the largest decline in the UV-Vis spectrum, and decreases the amount of iron sludge. Q-TOF analysis revealed that the primary eight organic compounds in the wastewater are phenolic or contain reducible functional groups such as aldehyde, carbonyl, carboxyl, carbon-carbon double bond, or ester. By monitoring changes in the COD removal rate and pH, Fe3+/Fe2+, H2O2, and others over time, the mechanism of organic matter removal in the Fe3+/H2O2 system is proposed: the reducible organic matter reduces Fe3+ to Fe2+, enhancing the Fe3+/Fe2+ cycle, and the generated Fe2+ reacts with H2O2 to remove organic pollutants via the Fenton reaction. Optimal operating conditions are identified as Fe2(SO4)3 dosage of 1.0 g/L, H2O2 dosage of 50 mol/L, reaction temperature of 30 °C, and initial pH of 6.8 using the controlled variable method. Under these conditions, after 60 minutes, the treatment shows significant COD, TOC, TN, and NH3–N removal efficiencies, a significant reduction in color, and an increase in biodegradability, with the B/C ratio rising from 0.17 to 0.47. This study confirms the viability of using a self-reduction Fe3+/H2O2 system for phenolic coal chemical wastewater, reducing operating costs and providing a theoretical foundation for further research and engineering applications.